Lexical‐Semantic Organization in Bilingually Developing Deaf Children With ASL‐Dominant Language Exposure: Evidence From a Repeated Meaning Association Task. Issue 4 (28th April 2016) - Mann, Wolfgang; Sheng, Li; Morgan, Gary
Abstract: This study compared the lexical‐semantic organization skills of bilingually developing deaf children in American Sign Language (ASL) and English with those of a monolingual hearing group. A repeated meaning‐association paradigm was used to assess retrieval of semantic relations in deaf 6–10‐year‐olds exposed to ASL from birth by their deaf parents, with responses coded as syntagmatic or paradigmatic. Deaf children's responses in ASL and English were compared at the within‐group level, and their ASL was compared to the English responses of age‐matched monolingual hearing children. Finally, the two groups were compared on their semantic performance in English. Results showed similar patterns for deaf children's responses in ASL and English to those of hearing monolinguals, but subtle language differences were also revealed. These findings suggest that sign bilinguals' language development in ASL and English is driven by similar underlying learning mechanisms rooted in the development of semantic frameworks. Open Practices: This article has been awarded an Open Materials badge. Study materials are publicly accessible in the IRIS digital repository athttp://www.iris‐database.org . The ASL/English Vocabulary Test is available athttp://alsevt.com; access information can be obtained from the first author. Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki